COMPARE THE OUTCOME OF STENTING VERSUS NON-STENTING IN PATIENTS UNDERGOING LASER LITHOTRIPSY FOR URETERIC CALCULI - HASSAN, A; SHAKIL, O; YOUSAF, MH; HUSSAIN, QM; HAIDER, A; IQBAL , H (Biological and Clinical Sciences Research Journal, 2024)
Acute renal colic caused by ureteral calculi is one of the most common abdominal emergencies, accounting for 1% of emergency department visits. Ureteroscopic lithotripsy (URL) and extracorporeal shock wave lithotripsy (ESWL) are two widely used methods for the treatment of ureteral stones. Objective: To compare the outcome (mean pain score, hospital stay, and frequency of UTI of stenting versus non-stenting in patients undergoing laser lithotripsy for ureteric calculi. Methods: This randomised controlled trial was conducted at the Department of Urology, Shaikh Zayed Hospital, Lahore, over six months from 07-10-2020 to 07-04-2021. After approval from the hospital's ethical committee and informed consent, 248 (124 in each group) patients fulfilling the inclusion criteria were admitted to the Department of Urology, Shaikh Zayed Hospital, Lahore. Patients were inquired about their demographical information. A lower abdominal ultrasound determined the position of the stone in the kidney. Patients were randomised into two groups. Group A was placed with a stent while group B was taken as control means without a stent. Both groups compared the outcome on the 3rd post-operative day as a per-operational definition. All the data was collected through well-defined proforma. (Annexed). Pain score, hospital stay, and UTI were recorded (as per operational definition). Results: Out of 248 cases (124 in each group), mean age was calculated as 46.11 ± 7.96 years in Group-A and 46.90± 7.59 years in Group-B, 33.1 % (n=82) in Group-A and 26.2 % (n=65) in Group-B were male whereas 16.9 % (n=42) in Group-A and 23.8 % (n=59) in Group-B were females. Urinary tract infection was also studied; urinary tract infection was present in 10.9 % (n=27) in Group A and 2.4 % (n=6) in Group B. The data was stratified by age, gender, size, location of the stone, and the duration of the patient's disease. Conclusion: We concluded that the implantation of ureteral stents might influence the stone-free rate. However, stent-related complications are the most significant drawbacks of ureteral stenting in most patients.